2021
DOI: 10.3389/fnagi.2021.731180
|View full text |Cite|
|
Sign up to set email alerts
|

Microglia Mediate the Occurrence and Development of Alzheimer’s Disease Through Ligand-Receptor Axis Communication

Abstract: Alzheimer’s disease (AD) is a common neurodegenerative disease. Its onset is insidious and its progression is slow, making diagnosis difficult. In addition, its underlying molecular and cellular mechanisms remain unclear. In this study, clustering analysis was performed on single-cell RNA sequencing (scRNA-seq) data from the prefrontal cortex of 48 AD patients. Each sample module was identified to be a specific AD cell type, eight main brain cell types were identified, and the dysfunctional evolution of each c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 48 publications
(51 reference statements)
0
12
0
Order By: Relevance
“…The higher the level, the more protection against neurodegeneration [ 29 ]. The biological role of IGF1 is mediated through IGF1R, and previous studies have shown that the high IGF1R expression in AD brain tissue is associated with clinicopathology [ 30 ]. Quan et al identified BRWD1 and its corresponding biological processes involved in the development of AD by constructing an AD protein interaction network [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The higher the level, the more protection against neurodegeneration [ 29 ]. The biological role of IGF1 is mediated through IGF1R, and previous studies have shown that the high IGF1R expression in AD brain tissue is associated with clinicopathology [ 30 ]. Quan et al identified BRWD1 and its corresponding biological processes involved in the development of AD by constructing an AD protein interaction network [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Limited studies talked about the relationship between MAP4K4 and AD. Jian et al (2021) found MAP4K4 in glial cells could influence the occurrence and development of AD through ligand-receptor axis communication. Considering the protective role of inhibiting MAP4K4 in neurons, future research needs to investigate whether MAP4K4 could mediates the progression of AD in animal studies.…”
Section: Discussionmentioning
confidence: 98%
“…In this study, REPS1 was identified as a potential biomarker of both disorders and Ras signaling as one of the drivers of pathogenesis. Given that neurodegeneration involves complex networks of interacting genes and pathways ( Jian et al, 2021 ), we adopted a genomic rather than “candidate gene” approach to understanding the landscape of changes that may help explain AD and VD. Our results may aid in the early diagnosis, treatment and even prevention of these debilitating disorders.…”
Section: Discussionmentioning
confidence: 99%